PENETAPAN KAIDAH HUKUM BARU MELALUI YURISPRUDENSI: ANALISIS PUTUSAN KONTEMPORER TENTANG SENGKETA TATA USAHA NEGARA, PEMBAGIAN WARIS BEDA AGAMA, DAN INOVASI PERLINDUNGAN HAK DIGITAL SERTA GENDER DALAM PERKARA PIDANA DAN PERDATA - KAJIAN PUSTAKA - Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2025)
This study discusses the role of jurisprudence as a dynamic source of law in establishing new legal rules in Indonesia. The focus of the study is directed at analysing contemporary decisions related to administrative disputes, interfaith inheritance, and innovations in digital and gender rights protection in criminal and civil cases. Through a literature review method, this study describes how judges, through their critical decisions, contribute to the formation of legal norms that are responsive to social, cultural, and technological developments and the need for substantive justice. The results of the study show that jurisprudence is capable of filling regulatory gaps and encouraging more inclusive and progressive legal transformation, both in the context of strengthening good governance, respecting religious plurality, protecting digital rights, and promoting gender equality. This study emphasises the importance of jurisprudence as a vital instrument of legal reform to respond to the dynamics of modern society and build an adaptive and just national legal system